FINANCIAL MASTERY: INNOVATIVE STRATEGIES FOR MAXIMIZING CORPORATE WEALTH - Fitriani Fitriani; Ahmad Junaidi; Linda Ayu Oktoriza (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study explores innovative financial strategies designed to maximize corporate wealth and enhance financial stability amidst volatile economic conditions and rapid technological advancements. Key strategies analyzed include automated asset management, data-driven decision-making, advanced liquidity management, and modern risk mitigation through hedging. The research employs a qualitative approach, using data from corporate annual reports, journal articles, and expert interviews to provide a comprehensive understanding of these techniques. Findings reveal that integrating technology—such as artificial intelligence, big data analytics, and predictive modeling—into corporate financial practices not only optimizes resource allocation but also strengthens resilience against market fluctuations. Additionally, the study offers recommendations for financial practitioners on adopting these strategies, highlighting the importance of continuous adaptation to changing financial landscapes. These insights aim to assist corporations in making informed, strategic decisions that support long-term growth and stability. Further research is suggested to explore sector-specific applications and the long-term impacts of technology-driven financial innovations.